Analisis Penerapan PSAK 102: Akuntansi Murabahah: (Studi Kasus Pada BPRS Jam Gadang Bukittinggi dan BPRS Al-Makmur Payakumbuh) - Dhani, Putri Rahma; Illahi, Ilham (JIMP: Jurnal Ilmiah Manajemen Profetik, 2023)
This study aims to determine the application of murabahah accounting at PT. BPRS Jam Gadang Bukittinggi and PT. BPRS Al-Makmur Payakumbuh according to PSAK 102. This research is a comparative descriptive study (comparison) with an analytical approach. Data collection techniques used through interviews and documentation with informants who know the situation and conditions of the murabahah financing process at the BPRS. The results of this study, at PT. BPRS Jam Gadang Bukittinggi and PT. BPRS Al-Makmur in the application of recognition and measurement as well disclosure of murabahah transactions is not fully in accordance with PSAK 102. So the bank needs to re-evaluate so that the application of murabahah accounting by the bank can run and adjust to PSAK 102 regarding murabahah accounting. With the existence of a bank that does sharia-based transactions, it will make people more familiar and knowledgeagle in transactions, especially murabahah financing.